TEKNOLOGI PENGOLAHAN DAN PENGAWETAN JAHE SEBAGAI KETERAMPILAN GURU SMK DALAM UPAYA MENGEMBANGKAN KEWIRAUSAHAAN SEKOLAH - Yuriani, Yuriani (Universitas Negeri Yogyakarta, 2010)
This civil serving program was aimed to give alternative skill for vocational school`s teacher especially business and management group. It was hoped can develop entrepreneur`s school, especially in technology and processing and preservation technologies ginger. This activity follow by vocational school' teacher especially bussines and management group in Sleman district. There are SMK N 1 Tempel, SMK N 1 Godean, SMK Muhammadiyah 2 Moyudan, SMK Muhammadiyah 1 Tempel, SMK N 1 Depok, SMK YPKK 1 Sleman, dan SMK YPKK 2 Tempel. Twenty teacher have deputy of the sample to this program. The teaching method which is used to support this program successfully are speech, answering a question, practice, and industrial survey. The practice was done twice by making seven kinds product of ginger. The result of civil service program by programmer and followers is very satisfying. It can be seen by absence and follower's anthusiasm. The result of practice are well and maximum. Product which is made from ginger with good procedure